2022
DOI: 10.3390/su14169826
|View full text |Cite
|
Sign up to set email alerts
|

Urban Living Labs and Critical Infrastructure Resilience: A Global Match?

Abstract: The challenges to public policy brought by climate change are some of the biggest challenges for cities around the world. These challenges are costlier and more substantial for low-income communities given the existence of their greater social and economic vulnerability. Among the existing tools, this paper highlights the role played by urban living labs (ULLs), which have been discussed in the literature as a booster of urban resilience in a more sustainable direction. By considering ULLs as strategic institu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…. are quite different from those in the European context” (Amorim et al, 2022, page 11). The edited book by Marvin et al (2018a) also contains case studies of ULs in Africa and Asia but their comparative results are limited.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…. are quite different from those in the European context” (Amorim et al, 2022, page 11). The edited book by Marvin et al (2018a) also contains case studies of ULs in Africa and Asia but their comparative results are limited.…”
mentioning
confidence: 88%
“… 20. In their literature review of ULLs, Amorim et al (2022) found that 95 per cent of the studies in their sample covered ULLs in the global North (86 per cent in Europe) and concluded that “ULLs can be characterized as a European phenomenon” with the cities of Amsterdam and Rotterdam together having more ULLs than any country (Amorim et al, 2022, page 9). …”
mentioning
confidence: 99%